2014
DOI: 10.1158/0008-5472.can-13-2033
|View full text |Cite
|
Sign up to set email alerts
|

Auranofin Induces Lethal Oxidative and Endoplasmic Reticulum Stress and Exerts Potent Preclinical Activity against Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) exhibits high remission rates after initial chemoimmunotherapy, but with relapses with treatment, refractory disease is the most common outcome, especially in CLL with the deletion of chromosome 11q or 17p. In addressing the need of treatments for relapsed disease, we report the identification of an existing U.S. Food and Drug Administration-approved small-molecule drug to repurpose for CLL treatment. Auranofin (Ridaura) is approved for use in treating rheumatoid arthritis, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
211
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(228 citation statements)
references
References 47 publications
10
211
1
6
Order By: Relevance
“…Data sets of genes with the altered expression profile derived from the gene expression microarray analyses were imported into the Ingenuity Pathway Analysis (IPA) Tool (Ingenuity Systems, Redwood City, CA). 39 Within this gene list, IPA identified the top 5 most perturbed gene networks in the MO2058 cells following treatment with JQ1 and assigned a score for these associated network functions (supplemental Table 2). The score (eg, a score of 57) assigned by the IPA indicates the probability (1 in 10 57 ) that the focus-genes in the data set are grouped together in a perturbed network due to random chance alone.…”
Section: Ba-mediated Growth Inhibition and Lethality Of MCL Cellsmentioning
confidence: 99%
“…Data sets of genes with the altered expression profile derived from the gene expression microarray analyses were imported into the Ingenuity Pathway Analysis (IPA) Tool (Ingenuity Systems, Redwood City, CA). 39 Within this gene list, IPA identified the top 5 most perturbed gene networks in the MO2058 cells following treatment with JQ1 and assigned a score for these associated network functions (supplemental Table 2). The score (eg, a score of 57) assigned by the IPA indicates the probability (1 in 10 57 ) that the focus-genes in the data set are grouped together in a perturbed network due to random chance alone.…”
Section: Ba-mediated Growth Inhibition and Lethality Of MCL Cellsmentioning
confidence: 99%
“…It showed good activities against multidrug‐resistant bacteria, including methicillin‐resistant Staphylococcus aureus (MRSA) and K. pneumoniae (Harbut et al , 2015; Sun et al , 2016b). Auranofin also exhibited activities against other diseases including HIV/AIDS (Chirullo et al , 2013), and some parasitic diseases (Debnath et al , 2012), as well as Alzheimer's disease, Parkinson's disease (Madeira et al , 2013; Madeira et al , 2014) and cancer (Fiskus et al , 2014). Notably, auranofin was evaluated in human clinical studies for gastrointestinal protozoa, HIV, and cancer.…”
Section: Drug Repurposingmentioning
confidence: 99%
“…A recent study showed that mitochondrial TrxR contributes to tumor growth through the HIF-1 pathway (64), supporting the idea that mitochondrial redox signaling is important for tumorigenesis. Conversely, the TrxR inhibitor auranofin partially inhibits the growth of leukemia and relapsed Hodgkin lymphoma cells in vitro (65,66). TrxR inhibitors may generally promote apoptosis or differentiation.…”
Section: The Trx and Gsh Systems In Cancermentioning
confidence: 99%